Hot Water Washing Pre-Treatment Effects on Hot Air-Drying Process of Food Waste - Aziz, Khalida; Qaisari, Suhrab Nikjo (Journal for Research in Applied Sciences and Biotechnology, 2024)
The study aims to determine the effects of pre-treatment and temperature on the drying behavior of food waste. The collected food waste was pre-treated by soaking in warm distilled water at 50°C for 10 minutes before the hot air-drying process at 70°C and 85°C. A hot air dryer at different drying times and temperatures were used to measure the food waste until no noticeable weight loss. In the beginning, the moisture content fell quickly, and then progressively decreased with increasing drying time. Food waste at 85°C recorded the shortest drying time of 121 minutes to reach equilibrium compared to another drying parameter 70 °C. The equilibrium moisture content of pre-treated food waste with hot distilled water at a temperature of 70 ˚C was 0.609g H2O g-1 dry solid since the non-pre-treated food waste was 0.767 g H2O g-1 dry solid. The equilibrium moisture content of pre-treated food waste at 85˚C was 0.489 g H2O g-1 dry solid. In conclusion, washing pretreatment has a significant impact on the drying process because pretreated samples reach equilibrium faster than non-washed ones. Overall, Drying technologies are essential for reducing the moisture content of food waste, which is required for environmental sustainability and safety.